IMPLEMENTATION OF LESSON STUDY AS AN ATTEMPT TO IMPROVE ELEMENTARY STUDENTS’ WRITING SKILLS - Kusubakti Andajani; Yeni Yusella; Ade Eka Anggraini; Sri Untari; Slamet Arifin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Lesson study is a classroom learning system in which several teachers collaboratively plan, teach, observe, revise, and deliver the output from one class. Regarding the lesson study implementation, teachers wisely explore how students learn, think, and change their behavior as an outcome of learning. Lesson Study implementation may lead to teaching improvement as teachers become more knowledgeable on how their students learn and think as well as how the instruction affects their students’ thinking. During the lesson design phase, teachers exchange ideas about how students might react to each part of the lesson. This paper presents a series of codes theoretically based on systematic documentation from teachers’ various learning and change aspects (knowledge and beliefs, professional learning communities, resources) in the cross-context lesson studies. Following the lesson observation research, teachers critically analyze collected data regarding the students learning and draw evidence-based implications to improve teaching instruction. This paper describes the influence of Lesson Study as an attempt to improve third-grade students’ writing skills. Data are collected through observation, interview, field notes, and direct practice. The implementation results of the Lesson Study for the third-grade students from February 2nd to March 7th, 2023, indicate that writing enhancement with capital capability increased to 12.68%, the use of punctuation was 21.43%, and the formation of simple patterned sentences was 1,12%. Nevertheless, the use of standard vocabulary decreased to 0.39%. Meanwhile, the observations during the process indicate the overall data of Lesson Study implementation as an attempt to increase students’ writing skills at 3.11%. The learning process that explores students' learning potential in improving their writing skills implies a positive result in their progress. Habit and practice on an ongoing basis can improve students' writing skills.